31P NMR Spectroscopically Quantified Hydrogen‐Bonding Strength of Thioureas and Their Catalytic Activity in Diels–Alder Reactions. Issue 29 (10th September 2014) - Nödling, Alexander R.; Jakab, Gergely; Schreiner, Peter R.; Hilt, Gerhard
Abstract: The hydrogen‐bonding strength of a variety of commonly employed thiourea catalysts was quantified by using a trialkylphosphine oxide as a 31 P NMR probe. Simple diarylthioureas and more complex bifunctional amine‐ and hydroxy‐substituted thiourea derivatives were examined. Their catalytic activity was determined in a Diels–Alder reaction, and the obtained pseudo‐first‐order rate constants were correlated with the 31 P NMR chemical shifts. A linear correlation between both variables was observed throughout the functionalized thioureas. The 31 P NMR probe correlation fared better in comparison to a p K a correlation. Accordingly, the quantification presented herein by using a 31 P NMR probe offers an elegant way to estimate the catalytic activity of thiourea catalysts in hydrogen‐bond‐activated reactions such as the Diels–Alder reaction. Abstract : The correlation of 31 P NMR shift values [Δ δ ( 31 P)] for the determination of hydrogen‐bond strengths of thiourea derivatives with kinetic data [ln ( k rel )]of thiourea‐catalyzed Diels–Alder reactions is evaluated. A Hammett‐type plot provides a more reliable correlation than the correlation of kinetic data with the p K a values of the thiourea derivatives.